Bridging the Gap between AZF Microdeletions and Karyotype: Twelve Years’ Experience of an Infertility Center - Hamid Kalantari; Marjan Sabbaghian; Paraskevi Vogiatzi; Amarnath Rambhatla; Ashok Agarwal; Giovanni M. Colpi; Mohammad Ali Sadighi Gilani (The World Journal of Men's Health, 2023)
Purpose: Despite all past efforts, the current guidelines are not explicit enough regarding the indications for performing azoospermia factor (AZF) screening and karyotype, burdening clinicians with the decision to assess whether such tests are meaningful for the infertile male patient. These assessments can be costly and it is up to the healthcare practitioner to decide which are necessary and to weigh the benefits against economic/psychological harm. The aim of this study is to address such gaps and provide update on current management options for this group of patients. Materials and Methods: To address such gaps in male infertility management and to elucidate whether AZF screening is indicated in individuals who concomitantly harbor chromosomal abnormalities we conducted a retrospective cohort analysis of 10,388 consecutive patients with non-obstructive azoospermia (NOA) and severe oligozoospermia. Results: Previously, it has been suggested that all NOA cases with chromosomal defects, except males with 46,XY/45,X karyotype, have no indication for AZF screening. Our findings revealed that cases carrying the following chromosomal abnormalities inv(Y)(p11.2q12); idic(Y)(q11.2); 46,XY,r(Y); idic(Y)(p11.2) and der(Y;Autosome) (76/169; 44.9%; 95% CI, 37.7– 52.5) should also be referred for AZF deletion screening. Here, we also report the correlation between sperm count and AZF deletions as a secondary outcome. In accordance with previously reported data from North America and Europe, our data revealed that only 1% of cases with >1×106 sperm/mL had Y chromosome microdeletions (YCMs). Conclusions: In the era of assisted reproduction, finding cost-minimization strategies in infertility clinics without affecting the quality of diagnosis is becoming one of the top prioritized topics for future research. From a diagnostic viewpoint, the results reflect a need to reconsider the different karyotype presentations and the sperm count thresholds in male infertility guidelines as indicators for YCM screening during an infertility evaluation.